Evaluation of chemopreventive potential of Strobilanthes crispus against colon cancer formation in vitro and in vivo. Issue 1 (December 2015) - Al-Henhena, Nawal; Khalifa, Shaden; Ying, Rozaida; Ismail, Salmah; Hamadi, Riad; Shawter, Abdrabu; Idris, Azila; Azizan, Ainnul; Al-Wajeeh, Nahla; Abdulla, Mahmood; El-Seedi, Hesham
Abstract Background With cancer being one of the major causes of death around the world, studies are ongoing to find new chemotherapeutic leads. There are common mechanisms for colorectal cancer (CRC) formation. Several are connected with oxidative stress-induced cell apoptosis and others are related to imbalanced homeostasis or intake of drugs/toxins. Plants that have been used for decades in folk and traditional medicine have been accepted as one of the commonest sources of discovered natural agents of cancer chemotherapy and chemoprevention. The aim was to study the antioxidant and chemopreventive effects ofStrobilanthes crispus on colorectal cancer formation. Methods Five groups of rats were injected subcutaneously with AOM, 15 mg/kg body weight, each once weekly for 2 weeks. The cancer group was continued on 10 % Tween-20 feeding for 8 weeks. The standard drug group was continued on 35 mg/kg 5-fluorouracil intraperitoneal injection twice a week for 8 weeks, and the experimental groups were continued on 250 and 500 mg/kgS. crispus extract oral feeding for 8 weeks, respectively. The normal group was injected subcutaneously with normal saline once a week for 2 weeks, followed by oral administration of 10 % Tween-20 for 8 weeks. All the rats were sacrificed after 10 weeks. The colons were evaluated grossly and histopathologically for aberrant crypt foci (ACF). Gene expression was performed forBax, Bcl2, Defa24, Slc24a3, andAPC genes by real-time PCR.S. crispus and its fractions were evaluated for their chemopreventive effects against human colorectal adenocarcinoma cell line HT29 and cytotoxicity for normal human colon epithelial cell line CCD 841, and the active fraction was assessed for its components. Results We observed significant decrease in total colonic ACF formation, malonaldehyde (MDA) and lactate dehydrogenase (LDH), increase in superoxide dismutase (SOD), up-regulation ofAPC, Bax andSlc24a3, and down-regulation ofDefa24 andBcl -2 in rats treated withStrobilanthes crispus . Conclusion Our results support thein vivo protection ofS. crispus against CRC formation (azoxymethane-induced aberrant crypt foci) and suggest that the mechanism is highly specific to protect from oxidative insults and the following apoptotic cascade.